BRICS Development (Brazil, Russia, India, China and South Africa) in Global Political Economic Rules - Gustavo Gil da SILVA (International Journal of Science and Society, 2020)
BRICS is an organization to accommodate and accommodate the industrial threshold countries at the time (10 years ago), and the first time the term was used by US economist Jim O'Neal, an economist with global financial company Goldman Sachs, in 2001. BRIC is an acronym from Brazil, Russia, India, China and South Africa. The BRICS leaders insist that this group will be a force of change. BRICS countries want themselves as spokespersons for developing countries. The BRICS countries together now represent almost one fifth of the global economy.